Fractionated robotic radiosurgery for unfavorable nonfunctioning pituitary macroadenoma: 5-year outcomes from a single institution protocol - Bhatnagar, Akrita; Marin, Monica Pernia; Lischalk, Jonathan W.; Koh, Min Ji; Agazzi, Siviero; Suy, Simeng; Harris, Brent T.; Sharma, Susmeeta T.; Aulisi, Edward; Anaizi, Amjad; Khattab, Mohamed H.; Jean, Walter C.; et al. (Frontiers in Oncology, 2025)
ObjectiveNonfunctioning macroadenoma is a commonly diagnosed pituitary tumor. Resection is the favored treatment, with radiosurgery often utilized for residual or progressing disease. Long-term outcomes are established in the literature for single-fraction frame-based radiosurgery, but mature outcomes are lacking for fractionated frameless radiosurgery. We report our institution’s 5-year efficacy and toxicity results for unfavorable nonfunctioning pituitary macroadenoma patients treated with 5-fraction robotic radiosurgery.MethodsBetween 2010 and 2020, patients who completed 5-fraction robotic radiosurgery for the treatment of unfavorable nonfunctioning pituitary macroadenomas were included. A tumor was considered unfavorable if the gross tumor volume (GTV) was larger than 5 cc or if it closely approached a critical structure (optic apparatus, brainstem, or pituitary gland). Local control was calculated using the Kaplan–Meier method.ResultsTwenty predominantly female patients (60%), ages 21–77 (median: 53 years), were included in this study. All underwent primary resection at the time of diagnosis. The indication for radiosurgery was tumor progression (n = 14, 70%) or residual tumor after subtotal resection (n = 6, 30%). Eighty-five percent of patients treated with radiosurgery (n = 17) had cavernous sinus involvement. Median GTV was 3.4 cm3 (range: 0.3–20.8 cm3), and 40% of the tumors had suprasellar extension. A mean dose of 28.8 Gy (range: 25–30 Gy) was delivered to a median isodose line of 80% (range: 75%–89%). The median optic chiasm maximum point dose was 21.8 Gy (range: 12.0–25.0 Gy). Acute toxicity was minimal with eight patients (40%) developing short-lived headaches and one patient (5%) developing a brief ipsilateral sixth nerve palsy. There was no late radiation-induced neurologic or optic dysfunction identified in this cohort. At a median follow-up of 5 years, local control was 94%. There was one in-field failure pathologically confirmed following surgery for pituitary hemorrhage and two radiographically confirmed out-of-field failures in patients with larger tumors (>20 cc).ConclusionsThe treatment of unfavorable nonfunctioning pituitary macroadenoma with 5-fraction robotic radiosurgery provides excellent local control to date, with acceptable toxicity. However, tumors with GTVs greater than 20 cc may still require conventionally fractionated treatment with a margin to optimize local control.